Organisational learning, competitive strategy and export performance : a thesis presented in partial fulfilment of the requirements for a degree of Master of Management in Marketing at Massey University, Auckland, New Zealand - Chen, Kai (Massey University, 2012)
With the rise of global competition, organisations must acquire new knowledge and enhance their capabilities in response to fast changing market requirements. In international markets, it is vital for organisations to gather knowledge from both internal and external sources; however, few existing studies explore this topic in detail. This study employs organisational learning theory and competitive strategy theory to formulate a new organisational learning-competitive strategy-performance theoretical model concerning firms operating in the export sector. This research explores the mediating role of competitive strategies in the relation between organisational learning and export performance. This thesis also explores the effect of organisational learning on competitive strategies (low cost, differentiation and innovation) and performance, as well as the impact of competitive strategies on performance. The model was tested using the experience of 105 NZ exporting firms operating in a variety of host markets. The structural equation modelling method was employed as a key statistical analysis method for exploring the organisational learning-competitive strategy-performance path model. The empirical results indicate that export performance is significantly affected by low cost and differentiation competitive strategies, but that organisational learning factors (explorative and exploitative) have no direct effect on export performance. It is also confirmed that organisational learning factors (explorative and exploitative) can act as antecedents of competitive strategy factors (innovation, low cost and differentiation), as they have a significant impact on the choice of competitive strategy. The results confirm the mediation role of competitive strategy in the relation between organisational learning and performance. The outcomes of this thesis provide a new direction for future exporting research regarding organisational learning, competitive strategy and performance.
Keywords: Organisational learning; Competition; Export trading companies; New Zealand